Effect of Dulaglutide on HbA1c and Vit B12, on Alloxan-Induced Diabetes in Albino Mice - Najah Balaoo; Nouh Aljarari (AlQalam Journal of Medical and Applied Sciences, 2025)
Diabetes mellitus (DM) is a metabolic disorder caused by a defect in insulin secretion, insulin action, or both; insufficient production of insulin results in prolonged elevated blood sugar levels. Insulin is initially synthesized in the beta cells of the pancreas as a larger single-chain polypeptide precursor known as proinsulin. Types of diabetes: primary and secondary. Primary diabetes is divided into types 1 and 2; type 1 is treated with insulin, while type 2 is treated with sulfonylureas, meglitinides, incretins, DPP-4 inhibitors, thiazolidinediones (TZDs), alpha-glucosidase inhibitors (AGIs), insulin, and GLP-1 receptor agonists. Dulaglutide is a long-acting human GLP-1 receptor agonist. Its effects include glucose-dependent potentiation of insulin secretion, inhibition of glucagon secretion, delay of gastric emptying, and weight loss with metformin. 24 albino mice were obtained from the animal house University of Benghazi and kept breeding for the experiment, they were chosen according to their weight and ranged from 20-30gm g. Divided into 3 groups, group 1 takes a normal pallet diet, the other 2 groups received HFD for 2 weeks, then alloxan was injected into all groups except group 1. After that, measure blood sugar if more than 140 given drugs for group 3, Dulaglutide. Drugs are given for one month. After a month, mice were sacrificed, and HbA1c and vitamin B12 were investigated.